EXPLICITATION OF CONJUNCTIVE RELATION IN ENGLISH-INDONESIAN TRANSLATION; A CORPUS BASED STUDY - Nur Ayomi, S.S., M.Hum., Putu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2010)
This paper studies explicitation as one of the proposed universal of translated text, which can be seen from the rise in the level of cohesive explicitness in the target text. From the corpus of English-Indonesian translation, it is found that conjunctive relations tend to be explicitated in Indonesian TT of expository texts. Although there are also other types of shifts such as implicitation and meaning change, explicitation takes a bigger portion in the TT. Most types of conjunctive relations made more explicit are internal conjunctives, which show relations between meanings in the sense of representation of the speaker’s own ‘stamp’ on the situation and communicative situation of the text, especially the adversative contrastive connectives of avowal which give assertion of veracity and clarification to the text.